Análise da usabilidade de site com sequências didáticas para o ensino de grego clássico através de cordéis digitais - Brazil, Vicente Thiago Freire (2025)
The possibility of teaching a classical language such as ancient Greek constitutes a unique experience in popularizing classical culture. Gamification is still a low-use methodology for teaching classical letters around the world, in Brazil there is still no record of any e- games developed for this educational purpose that use easily accessible platforms and that use cordel as an instrument mediation and promotion of learning. The large number of specificities in classical Greek grammar and syntax is one of the biggest challenges for the language teaching-learning process. Oftentimes, mnemonic methods – very overwhelming and somewhat infantilizing – and the excess of ending tables make sacal learning and teaching a merely repetitive process. Given this very rich context, fundamental questions arise that guide this research: how have Brazilian teachers articulated the need to problematize classical culture? Are there differences in the way teachers in the areas of Languages and its technologies and Human Sciences use educational technologies to approach the classical tradition? How have new educational technologies benefited the teaching of classical culture according to experiences already recorded in scientific literature? Given the current state of affairs, the general objective of this work was to evaluate the usability of a website developed to promote didactic sequences that constituted a viable pedagogical strategy for literacy in classical Greek, as well as the popularization of classical culture in general. This is an ethnographic, descriptive study with a qualitative approach. The research was carried out between January 2024 and February 2024, with the purpose of developing and evaluating the usability of an educational and teaching resource that helps teaching Greek using strings. To evaluate the usability of the pedagogical platform that was developed, the SUS (System Usability Scale) was used. Very high usability results were achieved, through calculations using the SUS score, which enables the Educational Product both to expand content and for its immediate use in educational environments. In a future perspective, translations and activities derived from the use of the Educational Product will be disseminated through an ebook accessible free of charge online.